11. ASSESSMENT OF THE CURRENT SITUATION OF KNOWLEDGE, ATTITUDE AND PRACTICE ON PREVENTION OF HAND, FOOT AND MOUTH DISEASE AMONG MOTHERS WITH CHILDREN UNDER 5 YEARS OLD WHO ARE STUDYING AT VINH PHONG KINDERGARTEN, VINH THUAN DISTRICT, 2022 (Vietnam Journal of Community Medicine, 2023)
Objective: Describe the knowledge, attitude and correct practice on prevention of Hand, Foot andMouth disease of mothers with children under 5 years old studying at Kindergarten in Vinh PhongCommune, Vinh Thuan District.Methodology: A cross-sectional descriptive study using quantitative research methods, handing outself-filling forms Kindergarten Vinh Phong commune, Vinh Thuan district in 2022Results: General characteristics of mothers in the study: The mean age was 28.05 ± 5.2 years, theage group 22-35 years accounted for 55.1%. There are 58.7% mothers of children with high schooleducation and 23.9% mothers with college education or higher. Employees work and democracy,self-employment accounts for a high percentage (72.4%).94.9% of mothers had access to information about limb disease, mainly through mass media such asradio, newspaper, television, internet (63.8%).The percentage of mothers with correct knowledge is 33.3%; has true mode is 67.4% and theperformance is 18.1%. The percentage of mothers who are correct in all 3 areas is 13%.Conclusion: The percentage of mothers with correct knowledge is 33.3%; has true mode is 67.4%and the performance is 18.1%. The percentage of mothers who are correct in all 3 areas is 13%.
Keywords: The right knowledge, attitude and practice of Mrs.